Hubungan Kepatuhan Konsumsi Tablet Tambah Darah Dengan Kejadian Anemia Pada Remaja Putri - Fatmawaty Suaib; Sitti Sahariah Rowa; Wirdatul Adwiah (Direktorat Politeknik Kesehatan Makassar, 2024)
Anemia is a condition where the hemoglobin level in the blood is lower than normal due to a lack of essential nutrients, especially iron. The prevalence of anemia in Indonesia aged 5-14 years is 26.80%, aged 15-24 years is 32% and in South Sulawesi is 32%. Factors associated with anemia include low economic status, poor diet, and compliance with the consumption of blood supplement tablets. This study aims to determine the relationship between compliance with the consumption of blood supplement tablets and the incidence of anemia in young women. This type of research is descriptive correlational research using a cross sectional approach. The sample in this study was 31 female students of Muhammadiyah 9 Berua Middle School who were selected as samples. The statistical analysis used was the Che Square test. The results of the statistical test showed that the majority of young women had complied with taking additional blood tablets, namely 17 people (54.8%), the majority of young women did not experience anemia, namely 23 people (74.2%) and The relationship between compliance with consuming blood supplement tablets and the incidence of anemia shows a value of p=0.038 (p<0.05). Based on the results of statistical tests, it can be concluded that there is a significant relationship between compliance with consuming blood supplement tablets and the incidence of anemia in young women at Muhammadiyah 9 Berua Middle School